Time Management Performed by the Selected Volleyball Players of Senior High School in Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Through athletics, volleyball players can improve their physical fitness as well as their senseof teamwork and sportsmanship. It's interesting to note that once the K–12 curriculum wasestablished in the Filipino educational system, there wasn't much information in the literatureabout how senior high school students perform academically.Many researchers have investigated the challenges encountered by varsity athletes that affecttheir academic performance, and all of them have concluded that time management skills maybe necessary to keep up with the assignments from teachers and coaches. In addition, theymust strike a balance between their academic and athletic performance.The ability to prioritize tasks and make a "to-do list" is a skill that is increasingly important forvarsity athletes nowadays if they are to complete their daily tasks and academic assignmentson time and avoid any difficulties.
Keywords: Education